PEMANFAATAN GENERATIVE ARTIFICIAL INTELLIGENCE DALAM PENGEMBANGAN MATERI AJAR EKOTEOLOGI PAI: PELUANG, TANTANGAN, DAN IMPLIKASI PEDAGOGIS - Salsabila, Naila Rizqi; Shania, Nur; Khoiril, Nurussyifa; Lutfiyah; Ana, Nurlaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the concept of ecotheology in Islamic Religious Education (PAI), examine the use of Generative Artificial Intelligence (GenAI) in developing ecotheology-based teaching materials, and identify its opportunities, challenges, and pedagogical implications. This research adopts a qualitative approach using library research by reviewing relevant national and international literature published between 2020 and 2025. The findings show that ecotheology is strongly grounded in Islamic teachings through the concepts of tauhid, khalifah, amanah, and mizan, which serve as the basis for fostering students’ ecological awareness. GenAI also offers significant potential in material preparation, media development, differentiated learning, and assessment. However, its use raises challenges such as algorithmic bias, hallucination risks, teacher dependency, and academic ethics issues. Therefore, GenAI should be positioned as a pedagogical support tool under teacher supervision and guided by Islamic values.